Enhancing biomass and lipid productivity of a green microalga Parachlorella kessleri for biodiesel production using rapid mutation of atmospheric and room temperature plasma - Mostafa E. Elshobary; Hossain M. Zabed; Xianghui Qi; Rania A. El-Shenody (Biotechnology for Biofuels and Bioproducts, 2022)
Abstract Background Microalgae, with their high adaptability to various stress conditions and rapid growth, are considered excellent biomass resources for lipid production and biodiesel feedstocks. However, lipid yield and productivity of the natural strains are common bottlenecks in their large-scale use for lipid production, which can be overcome by evolving new strains using conventional and advanced mutagenic techniques. It is challenging to generate microalgae strains capable of high lipid synthesis through natural selection. As a result, random mutagenesis is currently considered a viable option in many scenarios. The objective of this study was to explore atmospheric and room temperature plasma (ARTP) as a random mutagenesis technique to obtain high lipid-accumulating mutants of a green microalga for improved biodiesel production. Results A green microalgal species was isolated from the Chinese Yellow Sea and identified as Parachlorella kessleri (OM758328). The isolated microalga was subsequently mutated by ARTP to obtain high lipid-accumulating mutants. Based on the growth rate and lipid content, 5 mutants (named M1, M2, M4, M5, and M8) were selected from 15 pre-selected mutants. These five mutants varied in their growth rate from 0.33 to 0.68 day−1, with the lipid content varying between 0.25 g/L in M2 to 0.30 g/L in M8 at 10th day of cultivation. Among the mutants, M8 showed the maximum biomass productivity (0.046 g/L/day) and lipid productivity (20.19 mg/L/day), which were 75% and 44% higher than the wild strain, respectively. The triglyceride (TAG) content of M8 was found to be 0.56 g/L at 16th day of cultivation, which was 1.77-fold higher than that of the wild strain. Furthermore, M8 had the highest saturated fatty acids (C16-18) with the lowermost polyunsaturated fatty acid content, which are favorable properties of a biodiesel feedstock according to international standards. Conclusion The mutant strain of P. kessleri developed by the ARTP technique exhibited significant improvements in biomass productivity, lipid content, and biodiesel quality. Therefore, the biomass of this mutant microalga could be a potential feedstock for biodiesel production.